2019
DOI: 10.1016/j.desal.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Cost evaluation and optimisation of hybrid multi effect distillation and reverse osmosis system for seawater desalination

Abstract: Item Type Article Authors Al-Obaidi, M.A.; Filippini, G.; Manenti, F.; Mujtaba, Iqbal M. Citation Al-Obaidi MA, Filippini G, Manenti F et al (2019) Cost evaluation and optimisation of hybrid multi effect distillation and reverse osmosis system for seawater desalination. Desalination. 456: 136-149. Rights AbstractIn this research, the effect of operating parameters on the fresh water production cost of hybrid Multi Effect Distillation (MED) and Reverse Osmosis (RO) system is investigated. To achieve this, an ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…It is worth noting that determining the SHTA is necessary to assess the dimensions, and in turn, this aids to evaluate the construction costs of the desalination plant. 19 Finally, the freshwater production was similarly predicted by both competitive models with a very small deviation from the actual data.…”
Section: Model Validationmentioning
confidence: 76%
“…It is worth noting that determining the SHTA is necessary to assess the dimensions, and in turn, this aids to evaluate the construction costs of the desalination plant. 19 Finally, the freshwater production was similarly predicted by both competitive models with a very small deviation from the actual data.…”
Section: Model Validationmentioning
confidence: 76%
“…The larger scales of the CWP plant might decrease the LCOE and LCOW of the system to the lower values. To consider the effect of the scale economy, the LCOE and LCOW of the three different configurations that is discussed earlier delivering the larger capacities using the following well known relationship [12]. where exponent 'n' was considered to be 0.82.…”
Section: Effects Of Plant Scalementioning
confidence: 99%
“…Results showed that placing the RO membrane process upstream in the hybrid system generates the overall best configuration in terms of the quantity and quality of produced fresh water. In a recent study by Al-Obaidi et al [12], an economic assessment and optimization of the best mentioned configuration [11] of the hybrid desalination systems were explored. Using the economic model, the variation of the overall fresh water cost with operating conditions, namely steam temperature and steam flow rate for the MED/TVC system and inlet pressure and flow rate of the RO system were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential that the project planners and desalination engineers provide cost analysis regularly for this business cases (Al-Obaidi et al 2019 , La Cerva et al 2019 ). The cost of water production includes all spending associated with project implementation consists of fixed and variable components.…”
Section: Introductionmentioning
confidence: 99%